2014
DOI: 10.1590/1414-462x201400020014
|View full text |Cite
|
Sign up to set email alerts
|

Atividades participativas em grupos de educação em saúde para doentes crônicos

Abstract: O Ministério da Saúde propôs a realização de grupos de educação em saúde para os portadores de hipertensão e diabetes. Apesar de essa prática ser executada em várias localidades, muitas vezes ela apresenta uma série de limitações. Diante disso, o objetivo deste estudo foi analisar os fatores que contribuem para a presença de estratégias participativas em grupos realizados para portadores de hipertensão arterial e diabetes mellitus. Trata-se de uma pesquisa quantitativa de delineamento transversal realizada com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…The discourses that aim to share knowledge among professionals and users and have as a characteristic a concept of health education that values collective constructions and respects the knowledge of the other, is based on the ideal of the Educação Popular em Saúde (Popular Education in Health) (9) . Popular Education in Health, in this perception, appeared in the 1950s, with Paulo Freire.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The discourses that aim to share knowledge among professionals and users and have as a characteristic a concept of health education that values collective constructions and respects the knowledge of the other, is based on the ideal of the Educação Popular em Saúde (Popular Education in Health) (9) . Popular Education in Health, in this perception, appeared in the 1950s, with Paulo Freire.…”
Section: Discussionmentioning
confidence: 99%
“…Health education also has the capacity to promote greater involvement and approximation of users with health professionals. This capacity is an important bracing for these activities (9) . In order for educational strategies to achieve the expected results, it is necessary to create a bond between educators and learners, allowing for trust and respect, which subsidizes the reach of comprehensive and problem-solving care (17) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research on activities developed in health education groups also revealed that participatory strategies occur less frequently than traditional ones. In addition, this type of approach, through lectures, produces low adherence of people to services, generating frustrations in professionals and, consequently, suspension of the practice of care (31) .…”
Section: Discussionmentioning
confidence: 99%